PERANAN APARATUR PEMERINTAHAN DALAM PELAYANAN PUBLIK: STUDI PENGGUNAAN APLIKASI SIBERAS DI DESA SIPODECENG - Ernawati Ernawati; Nurjannah Nonci; Akhmad Yasin; Muhammad Rais Rahmat Razak; Mutiah Khaerunnisa (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2026)
This study aims to analyze the role of village government officials in public services through the use of the SIBERAS application and to identify the obstacles faced by officials in its implementation in Sipodeceng Village, Baranti District, Sidenreng Rappang Regency. The research method used is descriptive qualitative with data collection techniques in the form of in-depth interviews, observation, and documentation. The data were analyzed using a thematic approach supported by NVivo coding to map the patterns of the role of officials, the use of the application, and its impact on village public services.The results showed that village officials played a fairly good role in supporting digital-based services, especially in terms of service attitude, responsibility, and initiative in helping the community. However, limitations were found in technical competence and clarity of task distribution, which caused some officials to experience difficulties in operating SIBERAS. This study also revealed a number of obstacles, such as dynamic system changes and low digital literacy among the community. Nevertheless, officials made various efforts such as socialization, assistance, and routine coordination to overcome these obstacles. Overall, the use of SIBERAS had a positive impact on improving the efficiency, transparency, and quality of village public services.